Salinity Influence on Radicle Length of Two Potato Genotypes - Gontariu, Ioan; Iorgu, Elena; Hoffman, Dan (European Journal of Applied Sciences, 2024)
Potato is the fourth most important food growth, after three of cereals: rice, wheat and maize. Ii is also one the most important source of food at world level, being an essential economic one in developing countries. In agriculture, salinity stress is one of the main abiotic stress factors affecting potatoes. This kind of stress causes changes in internal and external physiology of potato plants, resulting in a decrease of tubercle quality and production. Moreover, it may cause damages in all developing stages of potato, being extremely devastating in the expansion phase of the tubercle when the nutritional requirements are at maximum for its growth. The paper aims at characterizing the contribution of technological parameters to two of the most grown potato cultivars in Romania: Santé and Roclas, and at investigating the way in which salinity stress can affect their growing rhythm by analyzing its influence on the rate of root division.